Functional assistance for stress distribution in cell culture membrane under periodically stretching. (26th August 2021) - Dai, Zhi-Xuan; Shih, Po-Jen; Yen, Jia-Yush; Wang, I-Jong
Abstract: Dynamic cell cultures simulate the in vivo cell environment for a regular loading system with curtain strains. However, it is difficult to obtain strains that are suitable for cells without conducting multiple trials. This study develops a device that increases the strain gradient by changing the tensile section, in order to determine the effect of various cyclic strains on cultured human keratinocytes (HK) cells. This device is used to determine the effect of 3% and 5% cyclic strain and shear strain on cell proliferation and arrangement at 1 Hz. The results show that compared with static and 3% strain, a 5% cyclic strain better inhibits the proliferation of HK cells. Compared to the initial cell attachment when there is no specific directionality, the cells are aligned in the vertical stretching direction after cyclic stretching. This equipment increases the efficiency of the experiment and more intuitively maps the cell behavior and shape to the strain field and the response to the shear strain.